Dive site geology: DSV ALVIN (2006) and ROV JASON II (2007) dives to the middle-lower continental slope, northern Gulf of Mexico - Roberts, H H; Shedd, W; Hunt, J (Deep-Sea Research. Part II: Topical Studies in Oceanography, 2010)
Use of DSV ALVIN (2006) and ROV JASON II (2007) provided access to never observed or sampled sites of fluid-gas expulsion from the little-studied middle and lower continental slope of the northern Gulf of Mexico (below water depths of 1000 m). Dives were focused on 15 locations selected by 3-D seismic surface attributes and shallow subsurface geologic analyses. The linkage between highly positive seafloor reflectivity and hard bottoms proved to be an efficient indicator of potential sites of interest. Through observation and sampling of reflective sites, starting in the mid-1980s, it has become apparent that most hard bottoms on the northern Gulf's continental slope are created by the precipitation of authigenic carbonates at hydrocarbon seep sites. Access to the Bureau of Ocean Energy Management, Regulation and Enforcement's extraordinary archive of slope-wide 3-D seismic data made efficient site selection possible. From thousands of sites that display the characteristics of fluid-gas expulsion, 15 were observed and sampled during the 2006 and 2007 cruises. Water depths in which these 15 sites were located ranged from ∼2750 to ∼970 m. All sites exhibited evidence of hydrocarbon seepage or more rapid venting. Chemosynthetic organisms, authigenic carbonates, barite, gas hydrates, highly anoxic surface sediments, brine pools, and hydrocarbon-laced brine flows were identified and sampled. High-resolution acoustic Autonomous Underwater Vehicle (AUV) data, including multibeam bathymetry, side-scan sonar swaths, and chirp sonar subbottom profiles, were collected at four locations (AC601, WR269, GC852, and AT340). Data sets from the 2006 and 2007 dives resulted in a greatly improved understanding of both cross-slope and along-slope variability in the characteristics of fluid-gas expulsion sites and associated habitats. Our studies confirmed the importance of fluid-gas expulsion processes for sustaining chemosynthetic communities and impacting seabed geology on the middle and lower continental slope of the northern Gulf of Mexico.
Keywords: HOV Alvin (Human Occupied Vehicle); ROV Jason (Remotely Operated Vehicle)